Understanding internal driven factors of household intention to upgrade waste treatment system: a case study of small-scale cow farming in Le Chi Commune, Gia Lam, Ha Noi - Nguyen, Thi Huong Giang (H. : ĐHQGHN, 2018)
10 p.